Bioethanol production from agricultural residues as lignocellulosic biomass feedstock's waste valorization approach: A comprehensive review - Jayakumar, Mani; Gindaba, Gadissa Tokuma; Gebeyehu, Kaleab Bizuneh; Periyasamy, Selvakumar; Jabesa, Abdisa; Baskar, Gurunathan; John, Beula Isabel; Pugazhendhi, Arivalagan (The Science of the total environment, 2023)
Bioenergy is becoming very popular, drawing attention as a renewable energy source that may assist in managing growing energy costs, besides possibly affording revenue to underprivileged farmers and rural populations worldwide. Bioethanol made from agricultural residual-biomass provides irreplaceable environmental, socioeconomic, and strategic benefits and can be considered as a safe and cleaner liquid fuel alternative to traditional fossil fuels. There is a significant advancement made at the bench scale towards fuel ethanol production from agricultural lignocellulosic materials (ALCM). These process technologies include pretreatment of ALCM biomass employment of cellulolytic enzymes for depolymerizing carbohydrate polymers into fermentable sugars to effectively achieve it by applying healthy fermentative microbes for bioethanol generation. Amongst all the available process methods, weak acid hydrolysis followed by enzymatic hydrolysis process technique. Recovering higher proficient celluloses is more attractive in terms of economic benefits and long-term environmental effects. Besides, the state of ALCM biomass based bioethanol production methods is discussed in detail, which could make it easier for the scientific and industrial communities to utilize agricultural leftovers properly. [Display omitted] •Agricultural residues lignocellulosic biomass were major bioethanol feedstock materials•Agricultural residues could had been converted into benign bioethanol•Bioethanol and its impacts on environment were investigated•Life-cycle appraisal and techno-economic examination were studied